Gamifying Physical and Mental Health: An Umbrella Review of Pokémon GO’s Public Health Impacts - Krawczyk, Michał; Molenda, Marek Jarosław; Woszczyńska, Oliwia Brygida; Rycąbel, Paweł Maciej; Romaniuk, Mateusz; Wachowska, Maria; Paniak, Mateusz; Sowiński, Wojciech Jan; Szymura , Marta; Wojciechowska, Agnieszka Ewelina (Quality in Sport, 2025)
Regular physical activity plays a vital role in supporting physical, mental, and social well-being, particularly among younger populations. However, rapid technological advancements and the growing popularity of digital entertainment have led to increasingly sedentary lifestyles. Pokémon GO, an augmented reality (AR) game, has emerged as a potential tool to counteract this trend by encouraging outdoor activity and real-world social interaction. Despite numerous studies indicating positive effects of the game on physical activity, mental health, and social engagement, the existing research remains fragmented. This umbrella review aims to synthesize current evidence on the public health impact of Pokémon GO. By analyzing findings from systematic reviews, meta-analyses, and literature reviews, this study provides a comprehensive evaluation of the game’s influence on health-related behaviors. The review highlights Pokémon GO's potential to promote physical activity and social connectivity, while also acknowledging the need for further standardized, long-term studies to fully understand both its benefits and associated risks.